2017
DOI: 10.48048/wjst.2018.3058
|View full text |Cite
|
Sign up to set email alerts
|

Bioecology and Uses of Desert Truffles (Pezizales) in the Middle East

Abstract: Desert truffles grow naturally after rainfall during the season of Al-Wasm in arid and semi-arid districts of Saudi Arabia, Iraq, Kuwait, Qatar, Bahrain, United Arab Emirates, Syria, Jordan, Palestine, Lebanon, Egypt, Iran, Turkey, Tunisia, Algeria, Libya, and Morocco. Al-Wasm provides rainfall of more than 200 ml in September to October in the Arabian Peninsula, and is important for the early growth and appearance of desert truffles. The amount of truffles increases depending on the amount of rainfall, as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The authors suggested that ecological characteristics and putative host plants of the genus Helianthemum instead of morphological criteria would be the most useful characters to separate these lineages of Picoa. Similar distribution of desert tru es has been reported by many authors in Europe countries (Honrubia et al 1992;Moreno et al 1986Moreno et al , 2000Kovacs et al 2011;Bordallo et al 2013;Chevalier 2014;Bordallo and Rodriguez 2014, Bordallo et al 2015, 2018, in Northern African countries (Fortas and Chevalier 1992;Khabar et al 2001;Slama et al 2006;Sbissi et al 2011;Bradai et al 2014, Berkami et al 2017Bouzadi et al 2017;Zitouni-Haouar et al 2015, 2018 and Middle East and Arabian Peninsula countries (Alsheikh and Trappe 1983;Bokhary 1987;Pacioni and El-Kholy 1994;Mandeel and Laith 2007;Ammarellou and Sarem 2008;Kagan-Zur and Roth-Bejerano 2008;Barseghyan and Wasser 2010;Al-Thani 2010;Jamali and Banihashemi 2012;Al-Qarawi and Mridha 2012;Akyuz et al 2015;Zamborelli et al 2014;Türkoğlu andCastellano 2014, Kagan-Zur andAkyuz 2014;Owaid 2016Owaid , 2018Bawadekji et al 2016;Hashem et al 2018).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The authors suggested that ecological characteristics and putative host plants of the genus Helianthemum instead of morphological criteria would be the most useful characters to separate these lineages of Picoa. Similar distribution of desert tru es has been reported by many authors in Europe countries (Honrubia et al 1992;Moreno et al 1986Moreno et al , 2000Kovacs et al 2011;Bordallo et al 2013;Chevalier 2014;Bordallo and Rodriguez 2014, Bordallo et al 2015, 2018, in Northern African countries (Fortas and Chevalier 1992;Khabar et al 2001;Slama et al 2006;Sbissi et al 2011;Bradai et al 2014, Berkami et al 2017Bouzadi et al 2017;Zitouni-Haouar et al 2015, 2018 and Middle East and Arabian Peninsula countries (Alsheikh and Trappe 1983;Bokhary 1987;Pacioni and El-Kholy 1994;Mandeel and Laith 2007;Ammarellou and Sarem 2008;Kagan-Zur and Roth-Bejerano 2008;Barseghyan and Wasser 2010;Al-Thani 2010;Jamali and Banihashemi 2012;Al-Qarawi and Mridha 2012;Akyuz et al 2015;Zamborelli et al 2014;Türkoğlu andCastellano 2014, Kagan-Zur andAkyuz 2014;Owaid 2016Owaid , 2018Bawadekji et al 2016;Hashem et al 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Desert tru es are edible mushrooms (Ascomycota) which include several species of the genera Terfezia, Tirmania and Picoa producing hypogeous ascomata and growing especially in arid and semi-arid areas (Fortas and Chevalier 1992;Alsheikh 1994;Khabar et al 2001;Slama et al 2006;Mandeel and Laith, 2007;Ammarellou and Sarem 2008;Kagan-Zur and Roth-Bejerano 2008;Al-Thani 2010;Sbissi et al 2011;Jamali and Banihashemi 2012;Al-Qarawi and Mridha 2012;Akyüz et al 2012;Türkoğlu and Castellano 2014;Kagan-Zur and Akyuz 2014;Akyüz et al 2015;Owaid 2016Owaid , 2018Bawadekji et al 2016;Berkami et al 2017;Bouzadi et al 2017;Zitouni-Haouar et al 2018;Hashem et al 2018) but can be found also in other habitats as in temperate forests (Janex-Favre et al 1988;Honrubia et al 1992), in mediterranean scrubland (Riousset et al 2004) and in a wide range of habitats, such as temperate deciduous forests, conifer forests, prairies, or even heath lands (Moreno et al 2014) .These edible mushrooms are most appreciated for their nutritional and economic value, but also for their properties in traditional medicine particularly by local populations of North Africa, the Middle East and the Arabian Peninsula. Most desert tru es establish important mycorrhizal symbioses with different host plants, most often Cistaceae family with including different annual and perennial species of the genus Cistus and more especially Helianthemum spp.…”
Section: Introductionmentioning
confidence: 99%
“…Although the compositional details of truffles vary from species to species and area to area, carbohydrates and proteins are generally the most abundant nutrients in truffles [1]. Besides, minerals, fibers, amino acids, fatty acids, and fats account for a significant portion of truffle composition [7,43]. For example, a desert truffle genera Terfezia possessed 46-48 g/100 g of dry weight (DW) of carbohydrates, 32-35 g/100 g DW of protein, 14-15 g/100 g DW of ash, and 2.8-3.2 g/100 g DW of fat, while another desert truffle genera Tirmania exhibited lower protein (8-29 g/100 g DW) and ash content (5.1-5.3 g/100 g DW) but higher carbohydrate (58-83 g/100 g DW) and fat content (4-7 g/100 g DW) [44][45][46][47].…”
Section: The Nutritional Profile Of Trufflesmentioning
confidence: 99%
“…Figure 1 showed that the lambda max was 410 nm with an absorbance of 1.091. The optical vision changed from very bright yellow to brown after the reaction between the truffle extract and AgNO 3 (1mM), which was considered as a sign that AgNPs had formed [19]. Changes in visual optical confirmed the synthesis of AgNPs from truffle extract [20,21], as seen in Figure 1.…”
Section: Resultsmentioning
confidence: 92%